Impetigo herpetiformis: a rare pregnancy-specific dermatosis - Mohsen M. A. Abdelhafez; Karim A. M. Ahmed; Mohd Nazri Mohd Daud; Mohammad Saffree Jeffree; Fairrul Masnah @ Kadir; Dg Marshitah Pg Baharuddin; Win Win Than; Mohd Firdaus Mohd Hayati; Kai, Xin Tay; Aya M. Eldiastey (SAGE Publications, 2022)
Impetigo herpetiformis (IH) is a pregnancy-specific dermatosis that is currently considered a form of generalised pustular psoriasis and mainly occurs in late pregnancy during the third trimester. IH presents as erythematous patches and pustules and might have systemic involvement. The disease may be associated with severe maternal, fetal, and neonatal complications. IH treatment is very challenging, however, various therapeutic options are available and effective for disease treatment.